Indomethacin-loaded lipid-core nanocapsules reduce the damage triggered by Aβ1-42 in Alzheimer’s disease models - Bernardi A (Dove Medical Press, 2012)
Andressa Bernardi,1,* Rudimar L Frozza,2,* André Meneghetti,2 Juliana B Hoppe,2 Ana Maria O Battastini,2 Adriana R Pohlmann,1,3 Sílvia S Guterres,3 Christianne G Salbego21Programa de Pós-Graduação em Ciências Farmacêuticas, 2Instituto de Ciências Básicas da Saúde, 3Instituto de Química, Universidade Federal do Rio Grande do Sul, Porto Alegre, Brazil*These authors contributed equally to this workAbstract: Neuroinflammation, characterized by the accumulation of activated microglia and reactive astrocytes, is believed to modulate the development and/or progression of Alzheimer’s disease (AD). Epidemiological studies suggesting that nonsteroidal anti-inflammatory drugs decrease the risk of developing AD have encouraged further studies elucidating the role of inflammation in AD. Nanoparticles have become an important focus of neurotherapeutic research because they are an especially effective form of drug delivery. Here, we investigate the potential protective effect of indomethacin-loaded lipid-core nanocapsules (IndOH-LNCs) against cell damage and neuroinflammation induced by amyloid beta (Aβ)1-42 in AD models. Our results show that IndOH-LNCs attenuated Aβ-induced cell death and were able to block the neuroinflammation triggered by Aβ1-42 in organotypic hippocampal cultures. Additionally, IndOH-LNC treatment was able to increase interleukin-10 release and decrease glial activation and c-jun N-terminal kinase phosphorylation. As a model of Aβ-induced neurotoxicity in vivo, animals received a single intracerebroventricular injection of Aβ1-42 (1 nmol/site), and 1 day after Aβ1-42 infusion, they were administered either free IndOH or IndOH-LNCs (1 mg/kg, intraperitoneally) for 14 days. Only the treatment with IndOH-LNCs significantly attenuated the impairment of this behavior triggered by intracerebroventricular injection of Aβ1-42. Further, treatment with IndOH-LNCs was able to block the decreased synaptophysin levels induced by Aβ1-42 and suppress glial and microglial activation. These findings might be explained by the increase of IndOH concentration in brain tissue attained using drug-loaded lipid-core NCs. All these findings support the idea that blockage of neuroinflammation triggered by Aβ is involved in the neuroprotective effects of IndOH-LNCs. These data provide strong evidence that IndOH-LNC treatment may represent a promising approach for treating AD.Keywords: Alzheimer’s disease, neuroinflammation, lipid-core nanocapsules, drug delivery, indomethacin, neuroprotection